Le déploiement d’un Système d’Information pour la coordination gérontologique de proximité dans le Haut-Rhin : une expérience encore perfectible - Christophe Humbert (Netcom)
We seek to define whether a process of technological innovation for gerontological coordination has generated an institutional innovation in its wake. While the French gerontological field has been described as mainly organized around the biomedical management of dependent old age, our analyses consist in determining whether the innovation work carried out has given the older adults concerned greater decision-making. No institutional innovations emerged according to our observations. Institutional rigidities remained throughout our fieldwork. The IS is thus an analyzer of the power relations between actors at the departmental level, as well as a catalyst for much more modest changes than those postulated, which were already in progress.